Insulinoma with seizures – a rare presentation of a rare tumour - Samartha Vinitha; Hegde Shreya; Reba Philipose Thoppil (International Journal of Medical Research and Review, 2016)
Insulinoma is a rare pancreatic endocrine tumour with an incidence of 4 per million population per year and is typically sporadic, solitary and less than 2 cms in diameter. Fewer than 5% of insulinomas are larger than 3 cms and are more likely to be malignant. Here we report a case of insulinoma in a female patient aged 57 years with a rare presentation of recurrent attacks of seizures, syncope and sweating along with episodes of hypoglycemia since 5 years. CT scan localized the tumour to the head of the pancreas and histopathology proved the diagnosis.